Bureau Of Mines Mineral Investigations In The Juneau Mining District, Alaska, 1984-1988 - Volume 2.- Detailed Mine, Prospect, And Mineral Occurrence Descriptions - Section C - West Lynn Canal Subarea - Introduction - Location, Access And Land Status - Albert H. Clough (The National Institute for Occupational Safety and Health (NIOSH), 2012)
The West Lynn Canal subarea of the Juneau Mining District (JMD) is defined by Lynn Canal on the east, Davidson Glacier to the north, Icy Strait to the south and the Glacier Bay National Park Boundary to the west (figs. C-l and C-2). This area extends along the main-land west of Juneau (across Lynn Canal) northerly, to approximately 20 miles south of the city of Haines. The only roads in the area are relatively new logging roads at the southern end constructed to support a U.S. Forest Service timber sale. There is also local road access near the community of Excursion Inlet. Access to the remainder of the region is either by boat, aircraft, or 'foot. Helicopters provide the only time effective access to all but the coastal parts of the West Lynn Canal subarea. Coastal areas may be reached by small boat or float aircraft. There is an unimproved dirt airstrip just north of the mouth of the Endicott River. This airstrip is suitable for use by light aircraft. The subarea lies within the Tongass National Forest and is managed by the Department of Agriculture, U.S. Forest Service. Approximately two-thirds of the forest lands are open to mineral entry under the current Tongass Land Management plan. The remaining forest lands comprise the Endicott River Wilderness area, which is closed to mineral entry. Private lands within the study area are sparse, with scattered homestead tracts along the coastal regions and in the Excursion Inlet area. Sealaska (Southeast Alaska Regional Native Corporation) also has land selections in the southern Chilkat Range. Tidal and submerged lands are owned by the State of Alaska.